Material Nanopartikel Fotokatalis Fe3O4/SiO2/TiO2 Untuk Degradasi Methylene Blue - Lenni, Nurma; Lubis, Ridwan Yusuf; ., Masthura (Fakultas Teknik UMSU, 2025)
This study aims to synthesize Fe3O4/SiO2/TiO2 photocatalytic material using the coprecipitation method with variations in calcination temperature and to investigate the effect of calcination temperature on the material characteristics as well as its ability to degrade methylene blue. The photocatalytic material was synthesized with a mass ratio of Fe3O4/SiO2/TiO2 of 3:2:2 and calcined at temperatures of 500 ˚C, 550 ˚C, and 600 ˚C. The material characterization was performed using X-Ray Diffractometer (XRD), Scanning Electron Microscope (SEM), and Ultraviolet-Visible (UV-Vis) Spectrophotometer. XRD results showed that increasing the calcination temperature led to an increase in crystal size from 28.01 nm at 500˚C to 30.06 nm at 600˚C. SEM analysis revealed morphological changes with an increase in particle size and agglomeration at higher temperatures, resulting in a denser and more porous surface. UV-Vis results showed that the FST600 sample, calcined at 600˚C, exhibited the highest methylene blue degradation rate, at 99.26%. This study demonstrates that higher calcination temperatures improve crystal size, enhance morphology, and increase the photocatalytic performance of Fe3O4/SiO2/TiO2 in methylene blue degradation.